Method for preparing AEI type zeolite molecular sieve membrane by secondary growth hydrothermal method
By using FAU molecular sieves as the aluminum source and homogeneous AEI seed crystals, and optimizing the hydrothermal synthesis conditions, AEI-type zeolite molecular sieve membranes with a high silicon-to-aluminum ratio were prepared. This solved the problems of low silicon-to-aluminum ratio and low separation selectivity of existing AEI zeolite membranes, and achieved efficient separation of organic acids and carbon dioxide.
Patent Information
- Application Number
- CN202512017444.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-02-06
AI Technical Summary
Existing AEI zeolite membranes have a low silica-to-alumina ratio and low separation selectivity, making it difficult to effectively separate carbon dioxide, acrylic acid/water, acetic acid/water, and acrylic acid/acetic acid/water solutions under acidic conditions.
FAU molecular sieves were used instead of traditional NaAlO2 as the aluminum source. Combined with homogeneous AEI seed crystals and optimized hydrothermal synthesis conditions, AEI-type zeolite molecular sieve membranes with high silicon-to-aluminum ratios were prepared. By adjusting the silicon-to-aluminum ratio in the membrane synthesis mother liquor, the density and stability of the membrane layer were improved.
The prepared AEI zeolite molecular sieve membrane exhibits high separation selectivity and acid resistance, especially in the separation of organic acid aqueous solutions and carbon dioxide gas.
Smart Images

Figure CN121466833A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of membrane separation technology, and relates to a method for preparing an AEI type zeolite molecular sieve membrane by secondary growth and a hydrothermal method. BACKGROUND
[0002] The separation of small molecule gases such as carbon dioxide (CO2) and the dehydration and purification of organic substances are two key separation challenges currently faced by the industry.
[0003] In terms of technology, although renewable energy power generation has made great progress, fundamental breakthroughs are still needed in the stability of the power system, long-term large-scale energy storage, zero carbonization of heavy traffic and key industrial processes (such as steel and cement production), and carbon capture, utilization and storage, in order to balance efficiency and economy.
[0004] Dehydration and purification of organic substances under harsh conditions such as acidity, high water content and high temperature have great demand in many fields such as chemical industry and new energy, such as dehydration of organic acid products such as acrylic acid and acetic acid, recovery of low-concentration acid-containing wastewater, purification of compounds involving strong acid in pharmaceutical and chemical industry, enrichment of low-concentration organic acid products in biological chemical industry, and recovery of solvents such as N-methyl-2-pyrrolidone (NMP) used in battery electrolyte in the new energy industry. Among them, the dehydration of acrylic acid and acetic acid is a typical model system for the purification of organic solvents under harsh conditions, and acetic acid and terephthalic acid (PTA) are among the top 50 basic chemical products in the world. China is the largest producer of these two types of chemicals (annual production of acetic acid is about 117 million tons, and PTA is about 60 million tons). The production of crude acetic acid (water content of 10-40 wt.%) needs to be dehydrated to high-purity acetic acid of 99.8 wt.%; in the production of PTA, dilute acetic acid solution needs to be concentrated and recycled. The distillation technology is extremely energy-consuming for the dehydration of acetic acid, and the separation and purification energy consumption accounts for 98% of the total energy consumption of acetic acid production. Acrylic acid is another important basic chemical product, which is prone to self-polymerization at a temperature higher than 80°C, so it is extremely energy-consuming to use vacuum low-temperature distillation.
[0005] Membrane separation technology is very suitable for the separation of carbon dioxide due to its high efficiency, low energy consumption and environmental protection, and can significantly reduce the energy consumption of the dehydration of various organic acids such as acetic acid, bringing significant economic and environmental benefits.
[0006] The AEI topological configuration was first discovered in aluminum phosphate molecular sieves (AlPO-18) and SAPO structure molecular sieves (SAPO-18) [1]This molecular sieve structure contains two six-membered rings, and its pore structure is a three-dimensional eight-membered ring pore structure. The diameter of the eight-membered ring pores is 0.38 nm × 0.38 nm. The pore diameter allows for the molecular sieve separation of small molecule gases and water with various organic acids such as acetic acid, formic acid, acrylic acid, oxalic acid, and glyoxylic acid. Furthermore, the hydrophilicity / hydrophobicity and acid resistance can be adjusted by regulating the silica-alumina ratio of the framework. Therefore, AEI-type zeolite molecular sieve membranes are ideal membrane materials for dehydrating organic matter under acidic conditions.
[0007] Currently, the main method for preparing AEI zeolite membranes is the homogeneous seed secondary hydrothermal growth method. This involves pre-coating an AEI seed layer onto a support and then immersing the pre-coated support in a synthesis solution for membrane preparation. This method separates the formation and growth of the crystal nucleus, which is beneficial for controlling the directional growth of the membrane. In recent years, few publications have reported the synthesis of AEI zeolite membranes. Only YUMA et al. (Membranes 2023, 13, 111) prepared an AEI-type molecular sieve dehydration membrane with a framework silica-alumina ratio less than 3. They isolated and developed an AEI-type molecular sieve dehydration membrane for use in a flow membrane reactor for the esterification reaction of acetic acid and ethanol. When separating aqueous acetic acid, the separation performance of water for acetic acid was low, with a separation selectivity of only 62, and the CO2 / CH4 separation selectivity was 35. The separation performance of the synthesized AEI membrane for aqueous acrylic acid solutions has not been reported. Considering the limiting relationship between the framework silica-alumina ratio of zeolite membranes and the acid resistance and hydrophilicity of zeolite membrane materials, increasing the framework silica-alumina ratio of zeolite membranes is one of the fundamental ways to improve the long-term acid resistance of AEI. Summary of the Invention
[0008] This invention provides a method for preparing AEI-type zeolite molecular sieve membranes for the efficient separation of carbon dioxide, acrylic acid / water, acetic acid / water, and aqueous solutions of polybasic organic acids such as acrylic acid / acetic acid / water. The purpose of this method is to solve the problems of low silicon-to-aluminum ratio and low separation selectivity of existing AEI membranes. By using FAU molecular sieves instead of traditional NaAlO2 as the aluminum source, a reasonable increase in the silicon-to-aluminum ratio of the AEI zeolite membrane framework is achieved. This provides a method for preparing AEI-type zeolite molecular sieve membranes with fewer defects, high density, and strong bonding with the support, resulting in a high silicon-to-aluminum ratio in the framework. Furthermore, this membrane exhibits excellent selectivity and acid resistance.
[0009] This method enables the controllable preparation of high-performance AEI molecular sieve membranes by using homogeneous AEI seeds and combined with optimized hydrothermal synthesis conditions. The AEI-type zeolite molecular sieve membranes exhibit good separation selectivity and acid resistance for the aforementioned organic acid aqueous solutions and carbon dioxide.
[0010] The technical solution of this invention is as follows:
[0011] A method for preparing AEI-type zeolite molecular sieve membranes via a secondary growth hydrothermal method includes the following steps:
[0012] Step (1) Preparation of large seed crystals of AEI-type molecular sieves:
[0013] Colloidal silica (silica sol) was used as the silicon source, FAU as the aluminum source, and 1,1,3,5-tetramethylammonium hydroxide piperidine as the organic template agent (OSDA). NaOH, the aluminum source, and deionized water were mixed thoroughly and stirred until clear. The organic template agent was added and mixed until homogeneous. Then, the silicon source was added dropwise, and the mixture was continuously stirred and aged to obtain a synthesis solution. The aged synthesis solution was placed in a hydrothermal reactor for high-temperature crystallization. The product was centrifuged, washed, and dried to obtain pure AEI-type molecular sieves, which were used as large seed crystals.
[0014] Step (2) Preparation of small seed crystals of AEI-type zeolite molecular sieve:
[0015] The AEI-type molecular sieve prepared in step (1) was ball-milled, and the ball-milled AEI-type molecular sieve was subjected to sedimentation treatment, centrifugation, and drying to obtain a small-sized AEI-type molecular sieve as a seed crystal.
[0016] Step (3) Preparation of AEI seed layer:
[0017] The AEI-type molecular sieves prepared in steps (1) and (2) were dispersed in a certain amount of deionized water as large and small seed solutions, respectively. Large and small seed solutions were then coated onto the surface of the porous carrier tube using a two-step variable-temperature hot immersion method. The large seed solution was dispersed in an aqueous solution, and the carrier tube was preheated by plugging both ends. The preheated carrier was vertically immersed in the large seed solution using a lifting method, held for a period of time, then uniformly removed, dried at room temperature, and cured at high temperature. Excess large seed solutions were wiped off the surface of the carrier tube with degreased cotton, and then small seed solutions were coated using the same steps as for the large seed solutions. The tube was dried at room temperature and cured at high temperature to obtain a smooth and defect-free AEI seed layer.
[0018] Step (4) Preparation of membrane synthesis solution:
[0019] Using colloidal silica (silica sol) as the silicon source, FAU molecular sieve prepared in step (1) or step (2) as the aluminum source, NaOH as the alkali source, and 1,1,3,5-tetramethylammonium hydroxide piperidine as the organic template agent, the organic template agent, alkali source, aluminum source and silicon source are added to water and mixed, stirred and aged to form a stable solution system, which is used as the membrane synthesis solution.
[0020] Step (5) Preparation of AEI-type zeolite molecular sieve membrane:
[0021] After coating the seed layer, the carrier tube is plugged at both ends, and the prepared synthesis solution is poured into the reactor. The carrier tube is then placed in the reactor for high-temperature crystallization. After the reaction, the membrane is washed with deionized water until neutral, dried, and calcined in an ozone or muffle furnace to remove OSDA, yielding an AEI-type zeolite molecular sieve membrane. The pervaporation performance of the AEI-type zeolite molecular sieve membrane for dehydrating organic acids and other organic substances can be controlled by adjusting the silica-alumina ratio of the membrane layer; and the silica-alumina ratio of the membrane layer can be controlled by adjusting the silica-alumina ratio in the membrane synthesis mother liquor.
[0022] In step (1), the molar ratio of the synthesis solution is SiO2: Al2O3: Na2O: OSDA: H2O = 1: (0.005~0.03): (0.2~0.7): (0.1~0.8): (5~90).
[0023] In step (1), the water bath aging temperature is 25~85℃ and the water bath aging time is 2~24 h.
[0024] In step (1), the hydrothermal crystallization temperature is 80~180℃ and the hydrothermal crystallization time is 3~16 days, preferably the hydrothermal crystallization temperature is 140℃ and the hydrothermal crystallization time is 3.5 days.
[0025] In step (1), the centrifuge speed is 8000~12000 rpm, the centrifugation time is 5~10 min, the drying temperature is 60~80℃, and the drying time is 12~24 h.
[0026] In step (1), the size of the AEI type zeolite molecular sieve obtained is 1.5~2 μm.
[0027] In step (2), the ball mill speed is 300~1500 r / min and the time is 1~6 days.
[0028] In step (2), the settling time is 2 to 24 days, preferably 15 days, the centrifuge speed is 10,000 to 12,000 rpm, the centrifugation time is 5 to 10 minutes, the drying temperature is 60 to 80°C, and the drying time is 6 to 48 hours.
[0029] In step (2), the size of the AEI type zeolite molecular sieve obtained by ball milling is 200~600 nm.
[0030] In step (3), the porous carrier is made of alumina, zirconium oxide or mullite, or stainless steel. The pore size of the porous carrier is 0.02 ~ 50 μm. Preferably, the carrier material is alumina or stainless steel, and the average pore size is 3 μm.
[0031] In step (3), the concentration of the prepared large seed solution is 0.1~5 wt.%, and the concentration of the small seed solution is 0.05~5 wt.%.
[0032] In step (3), the preheating temperature for coating large seed crystals is 100~160℃, the preheating time is 3~24 h, and the curing temperature is 100~160℃; the preheating temperature for coating small seed crystals is 60~120℃, the preheating time is 3~24 h, and the curing temperature is 80~160℃.
[0033] In step (3), the immersion time is 10-40 s when coating large seed crystals and 10-50 s when coating small seed crystals. Preferably, the immersion time for large seed crystals is 20 s and the immersion time for small seed crystals is 20 s.
[0034] In step (4), the molar ratio of each component in the membrane synthesis liquid system is SiO2: Al2O3: Na2O: OSDA:H2O = 1: (0.001~0.05): (0.01~0.4): (0.2~0.8): (10~100).
[0035] In step (4), the water bath aging temperature is 20~50℃ and the water bath aging time is 2~48 h, preferably 20 h.
[0036] In step (5), the crystallization temperature is 120~200℃ and the crystallization time is 12~96 h, preferably the crystallization temperature is 140℃ and the crystallization time is 36 h.
[0037] In step (5), the drying temperature is 40~60°C and the drying time is 5~24 h. The ozone calcination temperature is 150~300°C and the calcination time is 2~20 h. The muffle furnace calcination temperature is 400~560°C and the calcination time is 4~20 h.
[0038] The beneficial effects of this invention are:
[0039] Homogeneous seed-induced growth significantly reduces the nucleation barrier, avoids impurity phase formation, ensures a pure phase membrane with highly consistent crystal orientation, resulting in a membrane with fewer defects and higher density. The homogeneous seed crystal has a completely identical crystal structure to the subsequently grown membrane, resulting in low interfacial bonding energy and a stronger bond between the final membrane and the carrier, leading to better mechanical and thermal stability. It provides a uniform growth starting point, making the membrane preparation process more controllable and reproducible, which is beneficial for large-scale preparation. Using FAU molecular sieve instead of traditional NaAlO2 as the aluminum source allows for control of the silicon-to-aluminum ratio in the membrane synthesis mother liquor. Further increasing the silicon-to-aluminum ratio of the AEI zeolite membrane improves gas separation and pervaporation performance. The prepared AEI zeolite molecular sieve membrane exhibits high separation selectivity in gas separation and organic solvent dehydration, particularly for the dehydration of various organic acids and carbon dioxide gas separation. Attached Figure Description
[0040] Figure 1 The images are scanning electron microscope (SEM) images of AEI-type molecular sieve seed crystals of different sizes, where (a) is a large seed crystal and (b) is a small seed crystal.
[0041] Figure 2 This is the X-ray diffraction pattern of large crystals of AEI-type molecular sieve.
[0042] Figure 3 The XRD pattern of the synthesized AEI-type zeolite molecular sieve membrane.
[0043] Figure 4 The image shows a scanning electron microscope (SEM) image of the synthesized AEI-type zeolite molecular sieve membrane, where (a) is the surface and (b) is the cross-section. Detailed Implementation
[0044] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0045] Example 1
[0046] (1) Preparation of large crystals of AEI-type zeolite molecular sieve: The synthesis solution was prepared according to the formula of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.018: 0.3: 0.2:10. The solution was stirred and aged in a water bath at 60℃ for 5 h. The aged solution was then placed in a reaction vessel and crystallized in an oven at 140℃ for 3.5 d. After centrifugation, drying, and grinding, AEI-type molecular sieves with a size of 2 μm were obtained. The X-ray diffraction pattern of the large crystals of AEI-type molecular sieve is shown in the figure. Figure 2 As shown.
[0047] (2) Preparation of small AEI-type zeolite molecular sieve seeds: The prepared AEI-type molecular sieve was ball-milled at a speed of 500 r / min for 4 days. The ball-milled AEI-type molecular sieve was then subjected to sedimentation treatment for 15 days, followed by centrifugation, drying, and grinding to obtain small AEI-type molecular sieve seeds with a size of 200~600 nm. Scanning electron microscopy (SEM) images of the AEI-type molecular sieve seeds are shown below. Figure 1 As shown.
[0048] (3) Preparation of AEI seed layer: The AEI molecular sieves prepared in steps (1) and (2) were dispersed in a certain amount of deionized water to prepare 2.5 wt.% large seed solution and 1.5 wt.% small seed solution; the large and small seed layers were coated on the surface of the porous carrier tube by two-step variable temperature hot immersion: the large seed solution was dispersed, the two ends of the carrier tube were plugged and preheated at 140℃ for 8h, the preheated carrier was vertically immersed in the large seed solution for 20s by the lifting method, and then pulled out at a uniform speed and cured at 140℃ for 6h. After wiping away the excess large seed layer on the surface of the carrier tube with degreased cotton, the small seed layer was coated using the same steps as the large seed layer coating. The carrier tube was plugged at both ends and preheated at 80°C for 8 hours. The preheated carrier was vertically immersed in the seed solution for 20 seconds using the lifting method, and then pulled out at a uniform speed. It was dried at room temperature overnight and then cured at 120°C for 6 hours to obtain a uniform, dense and defect-free AEI seed layer.
[0049] (4) Preparation of membrane synthesis solution: The synthesis solution was prepared according to the molar ratio of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.0066: 0.2: 0.4:45 and a certain order of addition. A certain amount of NaOH and FAU crystals were weighed using an analytical balance, dissolved in deionized water, and stirred until clear in a constant temperature stirrer at 25℃, and recorded as solution A; a certain amount of organic template agent was weighed using an analytical balance, and recorded as solution B; silica sol, solution B and solution A were mixed and stirred for 10 min; and aged in a water bath at 25℃ with continuous stirring for 24 h to obtain the synthesis solution.
[0050] (5) Preparation of AEI-type zeolite molecular sieve membrane: The two ends of the carrier tube into which the seed layer was introduced in step (3) were plugged. The prepared synthesis solution was poured into the reactor, and the carrier tube was then placed in the reactor for crystallization reaction at 140℃ for 36 h. After the reaction, the zeolite membrane was washed with deionized water until neutral, dried, and then calcined at 473K for 6 h under an O3 gas flow containing 100-200 ppm O3 to remove OSDA. AEI-type zeolite molecular sieve membrane was obtained, as shown below. Figure 3 As shown.
[0051] The crystal structure of the AEI-type zeolite molecular sieve membrane is confirmed by the attached diagram. The membrane layer prepared in this example is relatively dense and smooth, with an average thickness of 6 μm.Figure 4 As shown, the dense membrane layer contributes to its excellent performance with acetic acid water. The AEI-type molecular sieve membrane prepared in Example 1 was subjected to a pervaporation test with 90 wt% acetic acid water at 75 °C, and its flux and separation factor were 0.32 kg / m³. 2 h, >10000; for a 10wt% acrylic acid / water solution at 70°C, the water permeation flux is 4.95 kg / m³. 2 h, the separation factor is 1342. For CO2 / CH 4、 The CO2 / N2 gas separation test showed a CO2 permeation flux of 2.73 × 10⁻⁶. -7 mol·m -2 ·s -1 ·Pa -1 The separation factor is 126. The separation coefficients for CO2 and N2 are 21.
[0052] Example 2
[0053] (1) Preparation of large crystal seeds of AEI type zeolite molecular sieve: The synthesis solution was prepared according to the formula of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.005: 0.2: 0.8:90. The solution was stirred and aged in a water bath at 85℃ for 2 h. The aged solution was placed in a reaction vessel and crystallized in an oven at 180℃ for 3 days. After centrifugation, drying and grinding, AEI type molecular sieve with a size of 2μm was obtained.
[0054] (2) Preparation of small AEI type zeolite molecular sieve seeds: The prepared AEI type molecular sieve was ball-milled at a speed of 300 r / min for 6 days. The ball-milled AEI type molecular sieve was then subjected to sedimentation treatment for 2 days, followed by centrifugation, drying, and grinding to obtain small AEI type molecular sieve seeds with a size of 200~600 nm.
[0055] (3) Preparation of AEI seed layer: The AEI molecular sieves prepared in steps (1) and (2) were dispersed in a certain amount of deionized water to prepare 0.1 wt.% large seed solution and 0.05 wt.% small seed solution; the large and small seed layers were coated on the surface of the porous carrier tube by two-step variable temperature hot immersion: the large seed solution was dispersed, the two ends of the carrier tube were plugged and preheated at 160℃ for 3h, the preheated carrier was vertically immersed in the large seed solution for 40s by the lifting method, and then pulled out at a uniform speed and cured at 160℃ for 6h. After wiping away the excess large seed layer on the surface of the carrier tube with degreased cotton, the small seed layer was coated by the same steps as the large seed layer coating. The carrier tube was plugged at both ends and preheated at 120°C for 3 hours. The preheated carrier was vertically immersed in the seed solution for 50 seconds using the lifting method, and then pulled out at a uniform speed. It was dried at room temperature overnight and then cured at 160°C for 6 hours to obtain a uniform, dense and defect-free AEI seed layer.
[0056] (4) Preparation of membrane synthesis solution: The synthesis solution was prepared according to the molar ratio of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.05: 0.01: 0.8:100 and a certain order of addition. A certain amount of NaOH and FAU crystals were weighed using an analytical balance, dissolved in deionized water, and stirred until clear in a constant temperature stirrer at 50℃, and recorded as solution A; a certain amount of organic template agent was weighed using an analytical balance, and recorded as solution B; silica sol, solution B and solution A were mixed and stirred for 10 min; and aged in a water bath at 50℃ with continuous stirring for 2 h to obtain the synthesis solution.
[0057] (5) Preparation of AEI-type zeolite molecular sieve membrane: Plug both ends of the carrier tube into which the seed layer was introduced in step (3), pour the prepared synthesis solution into the reactor, and then place the carrier tube into the reactor for crystallization reaction at 200℃ for 12h. After the reaction, wash the zeolite membrane with deionized water until neutral, dry it, and then calcine the obtained membrane at 573K for 2h under an O3 gas flow containing 100-200 ppm O3 to remove OSDA. AEI-type zeolite molecular sieve membrane is obtained.
[0058] The AEI-type molecular sieve membrane prepared in Example 2 was subjected to a pervaporation test at 75°C using 90 wt% acetic acid water. The membrane flux and separation factor were 0.15 kg / m³. 2 h, 1337; For a 10 wt% acrylic acid / water solution at 70°C, the water permeation flux is 1.21 kg / m³. 2 h, the separation factor is 899. For CO2 / CH 4、 The CO2 / N2 gas separation test showed a CO2 permeation flux of 1.71 × 10⁻⁶. -7 mol·m -2 ·s -1 ·Pa -1 The separation factor is 64. The separation coefficients for CO2 and N2 are 12.
[0059] Example 3
[0060] (1) Preparation of large crystal seeds of AEI type zeolite molecular sieve: The synthesis solution was prepared according to the formula of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.03: 0.7: 0.1:5. The solution was stirred and aged in a water bath at 25℃ for 24 h. The aged solution was placed in a reaction vessel and crystallized in an oven at 80℃ for 16 d. After centrifugation, drying and grinding, AEI type molecular sieve with a size of 2μm was obtained.
[0061] (2) Preparation of small seed crystals of AEI type zeolite molecular sieve: The prepared AEI type molecular sieve was ball-milled at a speed of 1500 r / min for 1 day. The AEI type molecular sieve after ball milling was subjected to sedimentation treatment for 24 days, and then centrifuged, dried and ground to obtain small seed crystals of AEI type molecular sieve with a size of 200~600 nm.
[0062] (3) Preparation of AEI seed layer: The AEI molecular sieves prepared in steps (1) and (2) were dispersed in a certain amount of deionized water to prepare 5 wt.% large seed solution and 5 wt.% small seed solution. The large and small seed solutions were coated on the surface of the porous carrier tube by two-step variable temperature hot immersion: The large seed solution was dispersed, the two ends of the carrier tube were plugged and preheated at 100℃ for 24 h, the preheated carrier was vertically immersed in the large seed solution for 10 s by the lifting method, and then pulled out at a uniform speed and cured at 100℃ for 6 h. After wiping off the excess large seed solution on the surface of the carrier tube with degreased cotton, the small seed solution was coated by the same steps as the large seed solution. The two ends of the carrier tube were plugged and preheated at 60℃ for 24 h, the preheated carrier was vertically immersed in the small seed solution for 10 s by the lifting method, and then pulled out at a uniform speed, dried at room temperature overnight, and cured at 80℃ for 6 h to obtain a uniform, dense, and defect-free AEI seed layer.
[0063] (4) Preparation of membrane synthesis solution: The synthesis solution was prepared according to the molar ratio of SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.001: 0.4: 0.2:10 and a certain order of addition. A certain amount of NaOH and FAU crystals were weighed using an analytical balance, dissolved in deionized water, and stirred until clear in a constant temperature stirrer at 25℃, and recorded as solution A; a certain amount of organic template agent was weighed using an analytical balance, and recorded as solution B; silica sol, solution B and solution A were mixed and stirred for 10 min; and aged in a water bath at 20℃ with continuous stirring for 48 h to obtain the synthesis solution.
[0064] (5) Preparation of AEI-type zeolite molecular sieve membrane: Plug both ends of the carrier tube into which the seed layer was introduced in step (3), pour the prepared synthesis solution into the reactor, and then place the carrier tube into the reactor for crystallization reaction at 120℃ for 96h. After the reaction, wash the zeolite membrane with deionized water until neutral, dry it, and calcine the obtained membrane at 423K for 20h under an O3 gas flow containing 100-200 ppm O3 to remove OSDA. AEI-type zeolite molecular sieve membrane is obtained.
[0065] The AEI-type molecular sieve membrane prepared in Example 2 was subjected to a pervaporation test with 90 wt% acetic acid at 75 °C. The membrane flux and separation factor were 0.11 kg / m³. 2h, 1000; for a 10 wt% acrylic acid / water solution at 70°C, the water permeation flux is 1.05 kg / m³. 2 h, the separation factor is 142. For CO2 / CH 4、 The CO2 / N2 gas separation test showed a CO2 permeation flux of 5.72 × 10⁻⁶. -7 mol·m -2 ·s -1 ·Pa -1 The separation factor is 28. The separation coefficients for CO2 and N2 are 8.
[0066] Comparative Example 1
[0067] This comparative example is the method used by Waseda University in Japan to prepare AEI-type zeolite molecular sieve membranes (Membranes 2023, 13, 111).
[0068] Porous alumina tubes were used as the carrier (outer diameter 10 mm; inner diameter 7 mm; average surface pore size 150 nm; Noritake, Japan). Both ends of the carrier tube were sealed with PTFE caps. The carrier was immersed in a seed solution in an AEI-type molecular sieve for 1 min. After drying at 343 K for 2 h, the immersion process was repeated. The resulting seed layer was calcined at 773 K for 3 h to inhibit the seed crystals from peeling off the carrier surface. The molar ratio of the synthesis solution was SiO2: Al2O3: Na2O: OSDA: H2O = 1:0.01: 0.1: 0.5:29.2. Sodium aluminate (31.0~35.0% Na2O, 34.0~39.0%, Kanto Chemical, Japan), tetraethyl orthosilicate (Sigma-Aldrich, Germany), sodium hydroxide (97%, Kanto Chemical, Japan), and TMPOH were mixed according to the above ratio to prepare the synthesis solution. The mixture was aged at 293 K for 24 hours before crystallization. The carrier tube was placed vertically in a stainless steel autoclave, and the aged synthesis solution was added. The autoclave was then hydrothermally treated at 433 K for 24 hours. After crystallization, the autoclave was cooled with flowing tap water. The membrane was washed with boiling water for 8 hours, dried overnight at 383 K, and then calcined at 573 K in a 200 ppm O3 stream for 60 hours to remove OSDA. The calcined membrane was used for separation measurements. The CO2 / CH4 gas separation of the AEI-type molecular sieve membrane prepared by this method was tested. Its CO2 permeation flux was 3.41 × 10⁻⁶. -7 mol·m -2 ·s -1 ·Pa -1 The separation factor is 35.
[0069] In summary, this method utilizes homogeneous seed-induced growth, significantly reducing the nucleation barrier, avoiding impurity phase formation, ensuring a pure phase membrane with highly consistent crystal orientation, resulting in a membrane with few defects and high density. Using FAU molecular sieve instead of traditional NaAlO2 as the aluminum source allows for control of the silicon-to-aluminum ratio in the membrane synthesis mother liquor. Further increasing the silicon-to-aluminum ratio of the AEI zeolite membrane enhances gas separation and pervaporation performance. The prepared AEI zeolite molecular sieve membrane exhibits high separation selectivity in gas separation and organic solvent dehydration, particularly for the dehydration of various organic acids and carbon dioxide gas separation.
Claims
1. A method for preparing AEI-type zeolite molecular sieve membranes via a secondary growth hydrothermal method, characterized in that, Includes the following steps: Step (1) Preparation of large seed crystals of AEI-type molecular sieves: Using colloidal silica as the silicon source, FAU as the aluminum source, and 1,1,3,5-tetramethylammonium piperidine hydroxide as the organic template agent OSDA; NaOH, aluminum source, and deionized water were mixed thoroughly and stirred until clear, the organic template agent was added and mixed until homogeneous, and then the silicon source was added dropwise, and the mixture was continuously stirred and aged to obtain a synthesis solution; the aged synthesis solution was placed in a hydrothermal reactor for high-temperature crystallization, and the product was centrifuged, washed, and dried to obtain pure AEI-type molecular sieves, which were used as large seed crystals; Step (2) Preparation of small seed crystals of AEI-type zeolite molecular sieve: The AEI-type molecular sieve prepared in step (1) was ball-milled, and the ball-milled AEI-type molecular sieve was subjected to sedimentation treatment, centrifugation, and drying to obtain small-sized AEI-type molecular sieves as seed crystals. Step (3) Preparation of AEI seed layer: The AEI-type molecular sieves prepared in steps (1) and (2) are dispersed in a certain amount of deionized water as large seed solution and small seed solution respectively. The large and small seed solutions are coated on the surface of the porous carrier tube by two-step temperature-varying hot immersion: the large seed solution is dispersed in the aqueous solution, the two ends of the carrier tube are plugged and preheated, and the preheated carrier is vertically immersed in the large seed solution by the lifting method. After a period of time, it is pulled out at a uniform speed, dried at room temperature, and cured at high temperature. After wiping away the excess large seed solution on the surface of the carrier tube with degreased cotton, the small seed solution is coated in the same way as the large seed solution, dried at room temperature, and cured at high temperature to obtain a smooth and defect-free AEI seed layer. Step (4) Preparation of membrane synthesis solution: Using colloidal silica as the silicon source, FAU molecular sieve prepared in step (1) or step (2) as the aluminum source, NaOH as the alkali source, and 1,1,3,5-tetramethylammonium piperidine as the organic template agent, the organic template agent, alkali source, aluminum source and silicon source are added to water and mixed, stirred and aged to form a stable solution system, which is used as the membrane synthesis solution; Step (5) Preparation of AEI-type zeolite molecular sieve membrane: After coating the seed layer, plug both ends of the carrier tube, pour the prepared synthesis solution into the reactor, and then place the carrier tube into the reactor for high-temperature crystallization. After the reaction, wash with deionized water until neutral, dry, and calcine the obtained membrane with ozone or muffle furnace to remove OSDA, thus obtaining the AEI type zeolite molecular sieve membrane.
2. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (1), the molar ratio of the synthesis solution is SiO2: Al2O3: Na2O: OSDA: H2O = 1: (0.005~0.03): (0.2~0.7): (0.1~0.8): (5~90).
3. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (1), the water bath aging temperature is 25~85℃ and the water bath aging time is 2~24 h; the hydrothermal crystallization temperature is 80~180℃ and the hydrothermal crystallization time is 3~16 d.
4. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (1), the centrifuge speed is 8000~12000 rpm, the centrifugation time is 5~10 min, the drying temperature is 60~80℃, and the drying time is 12~24 h.
5. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (1), the size of the AEI type zeolite molecular sieve obtained is 1.5~2 μm; in step (2), the size of the AEI type zeolite molecular sieve obtained by ball milling is 200~600 nm.
6. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (2), the ball mill speed is 300~1500 r / min, the time is 1~6 d; the settling time is 2~24 d; the centrifuge speed is 10000~12000 rpm, the centrifugation time is 5~10 min; the drying temperature is 60~80℃, and the drying time is 6~48h.
7. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (3), the porous carrier is made of alumina, zirconium oxide or mullite, or stainless steel. The pore size of the porous carrier is 0.02 ~ 50 μm. The concentration of the prepared large seed solution is 0.1 ~ 5 wt.%, and the concentration of the small seed solution is 0.05 ~ 5 wt.%.
8. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (3), the preheating temperature for coating large seed crystals is 100~160℃, the preheating time is 3~24 h, and the curing temperature is 100~160℃; the preheating temperature for coating small seed crystals is 60~120℃, the preheating time is 3~24 h, and the curing temperature is 80~160℃; the immersion time for coating large seed crystals is 10~40 s, and the immersion time for coating small seed crystals is 10~50 s.
9. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (4), the molar ratio of each component in the membrane synthesis solution system is SiO2: Al2O3: Na2O: OSDA: H2O = 1: (0.001~0.05): (0.01~0.4): (0.2~0.8): (10~100); the water bath aging temperature is 20~50℃, and the water bath aging time is 2~48 h.
10. The method for preparing AEI-type zeolite molecular sieve membranes by secondary growth hydrothermal method according to claim 1, characterized in that, In step (5), the crystallization temperature is 120~200℃ and the crystallization time is 12~96 h; the drying temperature is 40~60℃ and the drying time is 5~24 h; the ozone calcination temperature is 150~300℃ and the calcination time is 2~20 h; the muffle furnace calcination temperature is 400~560°C and the calcination time is 4~20 h.